2019
DOI: 10.1002/adfm.201807803
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Beads: Tissue‐Specific Extracellular Matrix Microbeads to Potentiate Reprogrammed Cell‐Based Therapy

Abstract: Microbeads have been utilized as efficient cell culture carriers and injectable scaffolds for cell transplantation. However, various polymers currently used to generate microbeads have limited applicability due to loss of biological functions and tissue‐specific effects. Here, a tissue bead platform is reported that can provide a tissue‐specific microenvironment to facilitate cell culture and potentiate cell therapy. Using a flow‐focusing microfluidic device, uniform‐sized tissue microbeads are fabricated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 72 publications
0
29
0
Order By: Relevance
“…Rothrauff et al (2017b) compared cartilage and tendon growth factors and reported promotion of tissue-specific differentiation across multiple cultures and also reported the distributions of various growth factors. Lee et al (2019) confirmed the decellularization of seven tissues including organs such as liver and heart. They fabricated uniform sized tissue microbeads using them ECM and reported three kinds of tissue-specific microbeads derived from liver, heart and muscle (Lee et al, 2019).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Rothrauff et al (2017b) compared cartilage and tendon growth factors and reported promotion of tissue-specific differentiation across multiple cultures and also reported the distributions of various growth factors. Lee et al (2019) confirmed the decellularization of seven tissues including organs such as liver and heart. They fabricated uniform sized tissue microbeads using them ECM and reported three kinds of tissue-specific microbeads derived from liver, heart and muscle (Lee et al, 2019).…”
Section: Discussionmentioning
confidence: 56%
“…Lee et al (2019) confirmed the decellularization of seven tissues including organs such as liver and heart. They fabricated uniform sized tissue microbeads using them ECM and reported three kinds of tissue-specific microbeads derived from liver, heart and muscle (Lee et al, 2019). These significantly enhanced the viability, lineage specific maturation, and functionality of each type of FIGURE 4 | Total protein and human growth factor analysis of soluble decellularized extracellular matrix (ECM) preparations.…”
Section: Discussionmentioning
confidence: 56%
“…[90] Microgels have been fabricated using a variety of biomaterials with different gelation mechanisms, including alginate, [91,92] agarose, [93] methacrylated hyaluronic acid, [94] poly(ethylene glycol) diacrylate (PEGDA), [95] poly(ethylene glycol) maleimide (PEGMAL), [96] GelMA, [97] self-assembled peptides, [98,99] and tissue-specific extracellular matrix (ECM). [100] Two-phase emulsions (e.g., water-in-oil) can be used to template the formation of microgels. [52] While this method is simple and high throughput, it generally produces microgels with a polydisperse size distribution.…”
Section: Cellularized Microcarriersmentioning
confidence: 99%
“…[90,97] A common system is the use of calcium ions to form crosslinked alginate microgels, however, other cellularized biomaterials can also be used by applying the gelation triggers in a contact [96] or non-contact fashion. [93] For example, agarose microdroplets can be set by cooling, [93] ECM and collagen microgels can be gelled by heating (generally to 37 °C), [100] while GelMA microdroplets can be photocrosslinked by UV irradiation. [101] Other fabrication methods include electro-assisted jetting and inkjet printing, [102][103][104] while micromolding [105] and photolithography [106][107][108][109] have been used to produce non-spherical microgels.…”
Section: Cellularized Microcarriersmentioning
confidence: 99%
“…Flow-focusing microfluidics was applied to generate microbeads for 3D culture and transplantation of reprogrammed cells. 76 Decellularized tissue-derived ECM solutions were used to encapsulate induced hepatic, cardiac, and myogenic cells all directly reprogrammed from fibroblasts in a tissue type-matched manner. 76 The tissue-specific ECM microbeads supported higher cellular viability and improved maturation and functionality, compared with the collagen type I microbeads.…”
Section: Microdevice Platformsmentioning
confidence: 99%